Gendered health, economic, social and safety impact of COVID-19 on adolescents and young adults in Nairobi, Kenya - Michele R. Decker (Public Library of Science (PLoS), 2021)
Background Infectious disease outbreaks like COVID-19 and their mitigation measures can exacerbate underlying gender disparities, particularly among adolescents and young adults in densely populated urban settings. Methods An existing cohort of youth ages 16–26 in Nairobi, Kenya completed a phone-based survey in August-October 2020 (n = 1217), supplemented by virtual focus group discussions and interviews with youth and stakeholders, to examine economic, health, social, and safety experiences during COVID-19, and gender disparities therein. Results COVID-19 risk perception was high with a gender differential favoring young women (95.5% vs. 84.2%; p<0.001); youth described mixed concern and challenges to prevention. During COVID-19, gender symmetry was observed in constrained access to contraception among contraceptive users (40.4% men; 34.6% women) and depressive symptoms (21.8% men; 24.3% women). Gender disparities rendered young women disproportionately unable to meet basic economic needs (adjusted odds ratio [aOR] = 1.21; p<0.05) and in need of healthcare during the pandemic (aOR = 1.59; p<0.001). At a bivariate level, women had lower full decisional control to leave the house (40.0% vs. 53.2%) and less consistent access to safe, private internet (26.1% vs. 40.2%), while men disproportionately experienced police interactions (60.1%, 55.2% of which included extortion). Gender-specific concerns for women included menstrual hygiene access challenges (52.0%), increased reliance on transactional partnerships, and gender-based violence, with 17.3% reporting past-year partner violence and 3.0% non-partner sexual violence. Qualitative results contextualize the mental health impact of economic disruption and isolation, and, among young women, privacy constraints. Implications Youth and young adults face gendered impacts of COVID-19, reflecting both underlying disparities and the pandemic’s economic and social shock. Economic, health and technology-based supports must ensure equitable access for young women. Gender-responsive recovery efforts are necessary and must address the unique needs of youth.